Reabilitar o "Esquecido": O Caso de Laboratório Marxer - Jacopo Riccardo Marchesoni (2016)
The object of the this work is the ''forgotten architecture'': the current state of neglect and damage of dozens of buildings that belong to the historic /architectural heritage, has led to analyze the increasing problem in the european territory. An important reflection on the practice and meaning of restoration, inspired by the motivational meetings with the architect Alberto Galardi , protagonist with his works of the Italian postwar . The proposed reflection and rehabilitation project focus on the typical structures of the Italian " Brutalist " period that used reinforced concrete as the main building material. A thorough rehabilitation , able to enhance the rich historical and architectural memory of the building, also to properly answer the new contemporary requests .